A novel aspect on different preservation methods for tomato paste by examining the protective effect of herb and spice oils - Cetiner, Ecenaz; Bayburt, Aysena; Acarali, Nil (ELSEVIER SCI LTD, 2023)
In this study, the effect of essential oils of herbs and spices on the protection of homemade tomato paste without additives was investigated. Garlic oil was used as plant essential oil and thyme oil was used as spice essential oil. Samples were kept without adding essential oils at the specified holding times in determined light and dark ambient conditions. After the test period of the prepared setups was completed, the amount of mold formed in the tomato paste was observed, and the optimum samples were determined as K4A4, K4K7, K4K13, K6K10, S6K4, S6K7, S6K10, S6A13 by weighing again and creating a %-time graph by mass. It was decided that thyme essential oil had a more protective effect in foods than garlic essential oil, with the analysis methods performed on optimum samples (Physical analysis, microbiological analysis, FT-IR, and TG DTA).
Keywords: Tomato paste; Garlic essential oil; Thyme essential oil; ANTIFUNGAL ACTIVITY; Chemistry; Food Science & Technology; Nutrition & Dietetics